Role of the Adrenal Medulla in Hypoglycaemia-Associated Autonomic Failure—A Diabetic Perspective - Manjula Senthilkumaran; Coen Koch; Mauritz Frederick Herselman; Larisa Bobrovskaya (Metabolites, 2024)
Hypoglycaemia-associated autonomic failure (HAAF) is characterised by an impairment in adrenal medullary and neurogenic symptom responses following episodes of recurrent hypoglycaemia. Here, we review the status quo of research related to the regulatory mechanisms of the adrenal medulla in its response to single and recurrent hypoglycaemia in both diabetic and non-diabetic subjects with particular focus given to catecholamine synthesis, enzymatic activity, and the impact of adrenal medullary peptides. Short-term post-transcriptional modifications, particularly phosphorylation at specific residues of tyrosine hydroxylase (TH), play a key role in the regulation of catecholamine synthesis. While the effects of recurrent hypoglycaemia on catecholamine synthetic enzymes remain inconsistent, long-term changes in TH protein expression suggest species-specific responses. Adrenomedullary peptides such as neuropeptide Y (NPY), galanin, and proenkephalin exhibit altered gene and protein expression in response to hypoglycaemia, suggesting a potential role in the modulation of catecholamine secretion. Of note is NPY, since its antagonism has been shown to prevent reductions in TH protein expression. This review highlights the need for further investigation into the molecular mechanisms involved in the adrenal medullary response to hypoglycaemia. Despite advancements in our understanding of HAAF in non-diabetic rodents, a reliable diabetic rodent model of HAAF remains a challenge.